2021
DOI: 10.13057/biodiv/d221039
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of leaves, flowers, and fruits extract of Etlingera elatior from Nagan Raya District, Indonesia against Escherichia coli and Staphylococcus aureus

Abstract: Abstract. Ernilasari, Walil K, Fitmawati, Roslim DI, Zumaidar, Saudah, Rayhannisa. 2021. Antibacterial activity of leaves, flowers, and fruits extract of Etlingera elatior from Nagan Raya District, Indonesia against Escherichia coli and Staphylococcus aureus. Biodiversitas 22: 4457-4464. Etlingera elatior is a medicinal plant that has been used by people in Indonesia, especially Acehnese people. Based on its secondary metabolites, E. elatior can be used as antibacterial agents against Gram-positive and Gram-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
(28 reference statements)
1
11
1
4
Order By: Relevance
“…There have been several previous studies on the topics discussed, including ( Zega et al, 2021), (Megawati, 2020), (Ernilasari et al, 2021), (Widowati et al, 2021), and (Dubale et al, 2023). Broadly speaking, previous research contains similarities and differences with this research.…”
Section: Literature Reviewmentioning
confidence: 67%
“…There have been several previous studies on the topics discussed, including ( Zega et al, 2021), (Megawati, 2020), (Ernilasari et al, 2021), (Widowati et al, 2021), and (Dubale et al, 2023). Broadly speaking, previous research contains similarities and differences with this research.…”
Section: Literature Reviewmentioning
confidence: 67%
“…The inflammatory process is believed to be inhibited through the suppression of cyclooxygenase-2 expression and the inhibition of transcriptional activation (NF-kB) and caspase-1 (Ernilasari et al, 2021;Hu et al, 2022). In addition, the alkaloids, phenolics, and flavonoids of kecombrang fruit extract can inhibit the growth of Staphylococcus aureus and Escherichia coli bacteria at a concentration of 2% through cell wall destruction (Ernilasari et al, 2021;Ghasemzadeh et al, 2015). Based on the results of the study, the potential of EE to inhibit bacterial growth is shown.…”
Section: Discussionmentioning
confidence: 99%
“…These include tannins, flavonoids, alcohols, aldehydes, and terpenes ( Chan et al , 2011 ). Because of its rich content, E. elatior is reportedly effective as an insecticide ( Tarigan et al , 2014 ), anticancer ( Ghasemzadeh et al , 2015 ), and antibacterial ( Ernilasari et al , 2021 ). However, its anti-trematode effect against F. gigantica has not been studied.…”
Section: Discussionmentioning
confidence: 99%